2012
DOI: 10.5194/hess-16-2437-2012
|View full text |Cite
|
Sign up to set email alerts
|

A generic method for hydrological drought identification across different climate regions

Abstract: Abstract. The identification of hydrological drought at global scale has received considerable attention during the last decade. However, climate-induced variation in runoff across the world makes such analyses rather complicated. This especially holds for the drier regions of the world (both cold and warm), where, for a considerable period of time, zero runoff can be observed. In the current paper, we present a method that enables to identify drought at global scale across climate regimes in a consistent mann… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
76
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 78 publications
(77 citation statements)
references
References 42 publications
(67 reference statements)
1
76
0
Order By: Relevance
“…tropical and arid regions in Africa and Asia). The analysis of drought characteristics can be done on a high number of grid cells with different climate using the method of Van Huijgevoort et al (2012b). The analysis of drought propagation features and the classification of hydrological droughts into types requires visual inspection and expert knowledge.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…tropical and arid regions in Africa and Asia). The analysis of drought characteristics can be done on a high number of grid cells with different climate using the method of Van Huijgevoort et al (2012b). The analysis of drought propagation features and the classification of hydrological droughts into types requires visual inspection and expert knowledge.…”
Section: Methodsmentioning
confidence: 99%
“…These case study areas correspond to natural headwater catchments in Europe with contrasting climate and catchment characteristics (Table 2). A short description of the case study areas is given in this subsection; more detailed descriptions can be found in Van Lanen et al (2008) and .…”
Section: Extraction Of Data For Case Study Areasmentioning
confidence: 99%
See 3 more Smart Citations